2014
DOI: 10.1007/s10029-014-1293-x
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin for prevention of intraoperative mesh contamination: demonstration of high bactericide effect (in vitro) and low systemic bioavailability (in vivo)

Abstract: Local application of gentamicin to meshes can completely prevent the growth of even gentamicin-resistant S. aureus strains in vitro. The systemic relevance of gentamicin in the clinical controls showed to be very low, without reaching therapeutic concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…Given that bacterial adhesion to the surface of the implanted natural polymer which becomes a source of nutrient substrates for microorganisms is a key stage of biofilm formation, coating of the implant with an antimicrobial drug is a promising strategy to prevent implant-associated infection [13,18]. In clinical practice of some countries, it has been proposed to impregnate or put an allosteric implant in an antibiotic solution just before use [24][25][26]. However, the efficacy of this method in reducing the risk of bacterial complications when using anti-adhesion barriers made of natural fibers has not been proved.…”
Section: Discussionmentioning
confidence: 99%
“…Given that bacterial adhesion to the surface of the implanted natural polymer which becomes a source of nutrient substrates for microorganisms is a key stage of biofilm formation, coating of the implant with an antimicrobial drug is a promising strategy to prevent implant-associated infection [13,18]. In clinical practice of some countries, it has been proposed to impregnate or put an allosteric implant in an antibiotic solution just before use [24][25][26]. However, the efficacy of this method in reducing the risk of bacterial complications when using anti-adhesion barriers made of natural fibers has not been proved.…”
Section: Discussionmentioning
confidence: 99%
“…The loading efficiency was estimated to be around 0.10e0.20 mg/cm 2 of prosthesis, which was sufficient to prevent contamination in an infected rabbit model [81]. Nonspecific physical adsorption of antibiotics [81,88,96,100], antiseptics [103] and enzymes [112,116] were reported by dipping or soaking aqueous solution containing the therapeutics directly on the meshes. Under such condition, the amount of antibacterial compound loaded depends mainly on the fluid adsorption capability of the mesh substrate.…”
Section: Dipping/soakingmentioning
confidence: 99%
“…Presoaking meshes in antibiotic solution does not lead to prolonged delivery, but aims principally in covering the critical early postoperative period to prevent bacterial adhesion to the materials, which was defined to be around 6 h [120]. A clinical study has shown that almost no antibiotic was detectable in patient's serum 24 h following the implantation of gentamicin presoaked meshes [96]. However, such technology has not yet shown clinical superiority over systemic antibiotic therapies [27], and further optimization should be sought to improve the therapeutic window and to prolong the duration of activity.…”
Section: Dipping/soakingmentioning
confidence: 99%
“…In a recent prospective randomized study by Yabanoğlu et al, investigating the effect of soaking the mesh in vancomycin before implantation on wound infection rates in ventral hernia repair, there was no difference between pre-soaking the mesh in vancomycin and saline. It has been observed that the release and degradation rates of the antimicrobial, the concentration in the wound are difficult to assess and reproduce with pre-soaking technique [76][77][78][79][80][81].…”
Section: Mesh Modificationsmentioning
confidence: 99%